Oil spillage and agriculture: effects of spent lubricating oil on soil nutrients and yield of soybeans {glycine max L. merril) (1998)
The toxicological effects of spent lubricating oil on Iwo Varieties of soybeans TGX I485-ID and TGX I448-2E Were investigated. Soil Chemical analysis before Planting and After harvest Revealed that there were variable decrease in the levels of Sodium (Na), Potassium (K), Zinc (Zn), Copper, (Cu), Nickel (Ni) and Manganese (Mn) with Increasing level of oil contamination. However, the Amount of Calcium (Ca), Magnesium (Mn), lron (Fe) and Cadmium (Cd) was found to have increased In the soil after harvest. Lead (Pb) and Chromium (Cr) were not detected in the contaminated and uncontaminated soils. Spent lubricating oil was found to cause delayed germination, reduced growth and yield Parameters In both varieties of soybeans; and with increasing level of oil contamination, the toxicity of the oil to soybeans were more pronounced